ANALISIS KINERJA SAHAM EMITEN DAL AM PERIODE SATU TAHUN SETELAH PENAWARAN PERDANA - Yusef Widya Karsana (Media Riset Akuntansi, Auditing & Informasi, 2009)
AbstractThe objective of this research is to examine short term performance of stock price after Initial Public Offering (IPO) in Indonesia, and also to know whether there are differences between weekly stock price performance and monthly stock price performance. The stock price performance is measured by abnormal return and wealth Relative. This research is an empirical study for the companies which performs IPO in the period of2000 to 2006. Re> ult of the analysis shows that all period tested, weekly performance and monthly performance, are outperformed. The comparation of the performance shows that weekly stock price performance is higher than monthly stock price performance.Keywords .'Initial Public Offering, weekly stock price performance, monthly stock priceperformance, abnormal return, wealth relative